Association of markers of vascular inflammation with blood pressure in midlife: the Hordaland Health Study. (14th October 2021) - Kringeland, E A; Tell, G S; Ulvik, A; Midtbo, H; Igland, J; Haugsgjerd, T R; Ueland, P M; Gerdts, E
Abstract: Background: Hypertension is a pro-inflammatory condition. A steeper rise in blood pressure (BP) has been observed in middle-aged women than men. However, sex-specific associations of vascular inflammation with midlife BP has not been much explored. Purpose: To test the association of markers of vascular inflammation, including neopterin, kynurenin:tryptophan ratio (KTR) and high sensitive C-reactive protein (CRP) with BP. Methods: Circulating levels of neopterin, KTR and CRP were measured in 2042 women and 1646 men aged 47–49 years from the community-based Hordaland Health study. The associations with systolic and diastolic BP were tested in sex-specific linear regression analyses and adjusted for body mass index, serum total- and high-density lipoprotein cholesterol, triglycerides, creatinine, physical activity, daily smoking and diabetes. Results: Compared to men, women had lower average BP (124/72 vs. 131/78 mmHg, p<0.001), higher plasma neopterin (7.5 vs 7.0 nmol/l, p<0.001) and comparable plasma KTR and serum CRP (both p>0.05). In multivariable analyses 1) higher neopterin was associated with higher diastolic BP in women, but not in men; 2) higher CRP was associated with higher systolic and diastolic BP in women, but not in men; 3) no association of higher KTR with BP was found in either sex (Table 1). A significant sex-interaction between neopterin and diastolic BP was found. Conclusion: Among participants in the Hordaland Health study, higher circulating levels of neopterin and CRP with higher BP was found among women only, suggesting that vascular inflammation contributes to BP elevation in middle-aged women. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): University of Bergen